Optimizing Pytixs Online Ticketing Applications with Microservices Implementation: An Approach from Monolithic Infrastructure - Abdullah Ridwan; Nur Ichsan Utama (Eduvest - Journal of Universal Studies, 2025)
Pytixs faces the challenge of defining and developing their online ticketing web application based on monolithic infrastructure and hosted on VPS (Virtual Private Server). This monolithic structure causes difficulties in scalability, maintenance, and the development of efficient new features. Therefore, migration to the microservices architecture hosted on AWS (Amazon Web Services) is considered a solution that can improve system performance, scalability, and flexibility. The study aims to evaluate and implement the transformation of Pytixs online ticketing web applications from a monolithic VPS-hosted infrastructure to a microservices architecture hosted on AWS. The migration process involves dismantling a monolithic service into several small, independent services, which communicate through the RESTful API. In addition, AWS provides a range of services that support microservices, such as Amazon ECS, Amazon Lambda, and Amazon RDS, which help in improving efficiency and infrastructure management. The results of this study show that migration to the microservices architecture hosted on AWS provides significant improvements in terms of system scalability and performance. In addition, application development and maintenance time is drastically reduced, allowing the development team to respond to business needs faster and more efficiently. This Pytixs case study provides practical guidance and insight to other companies facing similar challenges in upgrading their web applications.